Control of Molecular Orbital Ordering Using a van der Waals Monolayer Ferroelectric. Issue 9 (5th January 2023) - Amini, Mohammad; Silveira, Orlando J.; Vaňo, Viliam; Lado, Jose L.; Foster, Adam S.; Liljeroth, Peter; Kezilebieke, Shawulienu
Abstract: 2D ferroelectric materials provide a promising platform for the electrical control of quantum states. In particular, due to their 2D nature, they are suitable for influencing the quantum states of deposited molecules via the proximity effect. Here, electrically controllable molecular states in phthalocyanine molecules adsorbed on monolayer ferroelectric material SnTe are reported. The strain and ferroelectric order in SnTe are found to create a transition between two distinct orbital orders in the adsorbed phthalocyanine molecules. By controlling the polarization of the ferroelectric domain using scanning tunneling microscopy (STM), it is successfully demonstrated that orbital order can be manipulated electrically. The results show how ferroelastic coupling in 2D systems allows for control of molecular states, providing a starting point for ferroelectrically switchable molecular orbital ordering and ultimately, electrical control of molecular magnetism. Abstract : Controlling and tuning the orbital ordering in a single molecule using a monolayer ferroelectric substrate is realized. This is achieved by adsorbing transition metal phthalocyanine (TMPc) molecules on a ferroelectric monolayer SnTe. The orbital order is probed using low‐temperature scanning tunneling microscopy and scanning tunneling spectroscopy experiments, and it is demonstrated that it can be controllably changed by switching the polarization direction of the underlying ferroelectric monolayer.